KORELASI LAJU FILTRASI GLOMERULUS, HEMOGLOBIN, SATURASI OKSIGEN DAN KOMORBID DENGAN KADAR LAKTAT PASIEN PENYAKIT GINJAL KRONIS STADIUM TERMINAL - Tantri, Ni Luh; Lahmadi, Iqbal; W Soeatmadji, Djoko; -, Nursamsu (journal of internal medicine; Vol. 12, No. 3 September 2011)
Hyperlactatemia usually happen in Chronic Kidney Disease (CKD) patients and it can used as indicator how bad the oxygen perfusion to organs. Therapy for hyperlactatemia is Hemodialysis (HD). Some studies assume few factors that correlate to the level of lactate post HD, such as improving of Glomerulus Filtration Rate (GFR), level of hemoglobin (Hb), oxygen saturation and accompany diseases. An analytic cross sectional study was carried out in Saiful Anwar Hospital to deÞ ne correlation between GFR, level of Hb, oxygen saturation and accompany diseases with level of lactate post HD. Forty three samples were included. There were signiÞ cant correlation between level of lactate post HD with level of Hb (p = 0.000) and GFR (p = 0.006). With multivariate models, there were signiÞ cant correlation between level of lactate post HD with those factors (p = 0.000). Using linier regression entering those variables into model, it found formula level of lactate = 3.719 ! 0.196 (Hb) ! 0.053 (GFR). There was signiÞ cant correlation between between level of lactate post HD with GFR, Hb, oxygen saturation and accompany diseases.
Keywords: CKD, lactate, hyperlactatemia, hemodialysis